Chittagong, Bangladesh. (November 2015) - Mia, Md Aslam; Nasrin, Shamima; Zhang, Miao; Rasiah, Rajah
Highlights: Chittagong is the busiest seaport in the region and a major economic hub. Population growth and poor planning has caused serious environmental problems. An integrated framework of urban planning is needed. Abstract: Located in the southeast, metropolitan Chittagong is the second largest city in Bangladesh. Its strategic location as the busiest seaport in the region has made it a major economic hub attracting strong inflows of foreign investment into the production of apparel, ship breaking and oil refinery activities. The city boasts a deep harbor that supports strongly commerce, business and industrial activities. However, despite its rich scenic and natural endowments, population growth and poor planning has caused serious social, infrastructure and environmental problems so that about a third of its population live in slums. This profile captures the historical origin, and socio-economic and spatial development of Chittagong city. It also discusses the growing infrastructure and environmental challenges facing the city and the need for the introduction of an integrated multidimensional framework to make the city more livable than its present situation.